A non-catalytic function of carbonic anhydrase IX contributes to the glycolytic phenotype and pH regulation in human breast cancer cells. Issue 10 (28th May 2019) - Mboge, Mam Y.; Chen, Zhijuan; Khokhar, Daniel; Wolff, Alyssa; Ai, Lingbao; Heldermon, Coy D.; Bozdag, Murat; Carta, Fabrizio; Supuran, Claudiu T.; Brown, Kevin D.; McKenna, Robert; Frost, Christopher J.; et al.
Abstract : The most aggressive and invasive tumor cells often reside in hypoxic microenvironments and rely heavily on rapid anaerobic glycolysis for energy production. This switch from oxidative phosphorylation to glycolysis, along with up-regulation of the glucose transport system, significantly increases the release of lactic acid from cells into the tumor microenvironment. Excess lactate and proton excretion exacerbate extracellular acidification to which cancer cells, but not normal cells, adapt. We have hypothesized that carbonic anhydrases (CAs) play a role in stabilizing both intracellular and extracellular pH to favor cancer progression and metastasis. Here, we show that proton efflux (acidification) using the glycolytic rate assay is dependent on both extracellular pH (pHe ) and CA IX expression. Yet, isoform-selective sulfonamide-based inhibitors of CA IX did not alter proton flux, which suggests that the catalytic activity of CA IX is not necessary for this regulation. Other investigators have suggested the CA IX co-operates with the MCT transport family to excrete protons. To test this possibility, we examined the expression patterns of selected ion transporters and show that members of this family are differentially expressed within the molecular subtypes of breast cancer. The most aggressive form of breast cancer, triple-negative breast cancer, appears to co-ordinately express the monocarboxylate transporter 4 (MCT4) and carbonic anhydrase IX (CA IX). This supports a possible mechanism that utilizes the intramolecular H + shuttle system in CA IX to facilitate proton efflux through MCT4.